2003
DOI: 10.1016/s0378-3774(02)00165-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling root growth and the soil–plant–atmosphere continuum of cotton crops

Abstract: A simple and functional model to simulate cotton root growth is coupled to models of water balance and leaf water potential to predict the behavior of the soil-plant-atmosphere continuum (SPAC) of cotton crops. The root-growth model takes into account the dry matter partitioning to roots, root depth increase as a function of thermal time, soil mechanical resistance and soil water stress, and allows the inclusion of spatial variability of soil physical properties. The water balance model uses a cascade approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
2
5
0
1
Order By: Relevance
“…In our previous study, N and P absorption decreased significantly after shading, and the effects of shading after flowering were greater than those of shading before flowering (Cui et al, 2013a,b). Most roots were observed in the upper 30 cm of the soil and root biomass decreased with increasing soil depth (Table 3); this result is similar to that of Coelho (Coelho, Villalobos, & Mateos, 2003), who also reported that root biomass decreased as soil depth increased. Most of the roots accumulated in the top 30 cm, which is about 90% of the total root dry weight.…”
Section: Grain Yield and Yield Componentssupporting
confidence: 85%
“…In our previous study, N and P absorption decreased significantly after shading, and the effects of shading after flowering were greater than those of shading before flowering (Cui et al, 2013a,b). Most roots were observed in the upper 30 cm of the soil and root biomass decreased with increasing soil depth (Table 3); this result is similar to that of Coelho (Coelho, Villalobos, & Mateos, 2003), who also reported that root biomass decreased as soil depth increased. Most of the roots accumulated in the top 30 cm, which is about 90% of the total root dry weight.…”
Section: Grain Yield and Yield Componentssupporting
confidence: 85%
“…The SPAC principle has been used and verified extensively in earlier research [58][59][60][61]. Recently, Gao et al (2015) [62] testified that the SPAC principle is not only suitable for arid and semiarid areas but also for the relatively humid karst rocky desertification area in the southwest of China.…”
Section: Theoretical Basismentioning
confidence: 99%
“…However, at Day 55 water consumption was lower than the crop evapotranspiration. The results can be related to a soil-water balance model that describes the relationship between the water consumption and crop evapotranspiration to (Blizzard and Boyer 1980;Liu et al 1998;Coelho et al 2003).…”
Section: Potential Evapotranspiration and Water Consumptionmentioning
confidence: 99%